MODERN APPROACHES TO PREPARING CHILDREN WITH DISABILITIES FOR FAMILY LIFE (EXAMPLE OF MENTALLY WEAK CHILDREN) - Madina MansurovnaArslanova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In our country, a huge work is underway to provide comprehensive support for children with disabilities. The gradual preparation of children in the process of lifelong education for their future family life, based on the characteristics of their mental and physical development, is one of the most important factors in their socialization. This article deals with modern approaches to preparing children with disabilities for a future family life on the example of children with mental retardation.